Military innovation in the interwar period - Murray, Williamson; Millet, Alan R. (Cambridge University Press, 1996)
This study of major military innovations in the 1920s and 1930s explores differences in innovating exploitation by the seven major military powers. This volume of comparative essays investigates how and why innovation occurred or did not occur, and explains much of the strategic and operative performance of the Axis and Allies in World War II.